Training and knowledge transfer at the interface of cultures = Szkolenia a transfer wiedzy na styku kultur - Winkler, Renata (Zielona Góra: Faculty of Economics and Management Press)
The paper discusses different approaches to the problems of knowledge transfer. In the paper factors that influence crosscultural knowledge transfer with training is presented. It can be argued that the impact of national culture on the transfer of knowledge is less than the influence of such elements of the transfer process like: number of canal, source's willingness to share knowledge, sender's willingness to acquire knowledge, absorptive capacity of the receiver and to what degree Knowledge Resources was transformed.
Keywords: szkolenia; transfer wiedzy; wielokulturowość; training; knowledge transfer; multiculturalism